What can experiments tell us about how to improve governance? - Rachel M. Gisselquist; Miguel Ni\~no-Zarazúa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
In recent years, randomized controlled trials have become increasingly popular in the social sciences. In development economics in particular, their use has attracted considerable debate in relation to the identification of 'what works' in development policy. This paper focuses on a core topic in development policy: governance. It aims to address two key questions: (1) 'what have the main contributions of randomized controlled trials been to the study of governance?' and (2) 'what could be the contributions, and relatedly the limits of such methods?'. To address these questions, a systematic review of experimental and quasi-experimental methods to study government performance was conducted. It identified 139 relevant papers grouped into three major types of policy interventions that aim to: (1) improve supply-side capabilities of governments; (2) change individual behaviour through various devices, notably incentives, and (3) improve informational asymmetries. We find that randomized controlled trials can be useful in studying the effects of some policy interventions in the governance area, but they are limited in significant ways: they are ill-equipped to study broader governance issues associated with macro-structural shifts, national level variation in institutions and political culture, and leadership. Randomized controlled trials are best for studying targeted interventions, particularly in areas of public goods provision, voting behaviour, and specific measures to address corruption and improve accountability; however, they can provide little traction on whether the intervention is transferable and 'could work' (and why) in other contexts, and in the longer run.
Keywords: C93; D72; D73; H41; 330; randomised control trials; governance; development